From Manual to Digital: Modernizing the Sales Recording System for Growth at MSME Rumah Abon - Yuniarto, Aflah Ananda; Siregar , Ifan Wicaksana (Science Tech Group, 2025)
This study explores the process of digital transformation in sales recording systems within Micro, Small, and Medium Enterprises (MSMEs), focusing on the case of Rumah Abon, a traditional food business in Indonesia. Despite MSMEs’ vital contribution to the national economy, many still rely on manual recording methods, which create risks of human error, inefficiency, and poor decision-making capacity. Using a qualitative descriptive case study approach, data were collected through in-depth interviews, observation, and documentation involving eight key informants directly engaged in the sales cycle. The findings reveal systemic inefficiencies across six critical stages of the sales process: order acceptance, sales processing, shipping, cash receipts, internal control, and reporting. Manual practices led to fragmented information, weak internal controls, and limited analytical capabilities, ultimately constraining business growth. The study concludes that transitioning to a digital accounting information system significantly enhances recording accuracy, operational efficiency, and managerial decision-making. Theoretically, this research contributes to the literature by integrating the System Development Life Cycle (SDLC) and Technology Acceptance Model (TAM) to analyze the transition phase from manual to digital systems. Practically, it provides MSME owners, software developers, and policymakers with strategic insights and recommendations to ensure that digitalization is not merely technological adoption but a holistic process of organizational transformation.